2017
DOI: 10.1007/s00431-017-3063-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrical velocimetry for non-invasive monitoring of the closure of the ductus arteriosus in preterm infants

Abstract: The surgical closure of the PDA in preterm infants causes a transient deterioration of cardiac function linked to a documented decrease in the left ventricular output. The hemodynamic changes detected after pharmacological PDA closure are similar but those patients present a better clinical tolerance to changes in the cardiac output. What is Known: • Surgical ductus closure generates acute hemodynamic changes in cardiac output and left ventricular function. What is New: • The hemodynamic changes detected after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Various concerns regarding the accuracy of these non-invasive cardiac output monitors have been raised in adult and pediatric medicine ( 37 , 38 , 46 ). Despite this, these monitors have been used in neonatology in research and clinical environments for diverse scenarios: monitoring transition at birth ( 47 , 48 ), cardiac adaptation after birth ( 49 ), patent ductus arteriosus (PDA)diagnosis ( 50 ), PDA ligation ( 29 ), PDA medical therapy ( 51 ), monitoring congenital heart disease ( 52 , 53 ), managing neonatal hemodynamic shock ( 54 ) and sepsis ( 55 ), and to predict clinical outcomes ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various concerns regarding the accuracy of these non-invasive cardiac output monitors have been raised in adult and pediatric medicine ( 37 , 38 , 46 ). Despite this, these monitors have been used in neonatology in research and clinical environments for diverse scenarios: monitoring transition at birth ( 47 , 48 ), cardiac adaptation after birth ( 49 ), patent ductus arteriosus (PDA)diagnosis ( 50 ), PDA ligation ( 29 ), PDA medical therapy ( 51 ), monitoring congenital heart disease ( 52 , 53 ), managing neonatal hemodynamic shock ( 54 ) and sepsis ( 55 ), and to predict clinical outcomes ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Infants treated for a PDA were found to have lower mean BP, CO, and SV compared to untreated, but after adjustment for GA and birth weight, all parameters except mean BP were found to be non-significant. In contrast, Rodríguez et al (52) monitored infants undergoing treatment of PDA (three ibuprofen doses) using EC. They reported a significant decrease in CO indexed for body weight (0.24 vs. 0.29 L/kg/min; P 0.03) after 72 h. Hsu et al ( 53) found infants with PDA had higher pre-treatment baseline CO determined by EC compared to non-PDA infants.…”
Section: Patent Ductus Arteriosusmentioning
confidence: 99%
“…There is a similar study utilizing EC to monitor CO during attempted pharmacological closure of PDA by intravenous ibuprofen in preterm infants [23], of which, a fall in median CO EC from 290 to 240 ml/kg/min (17%) 72 h after the initiation of treatment was found. However, the study is limited by its small case number (6 responders) and a wide overlap of CO EC between baseline and 72 h after the first dose ibuprofen.…”
Section: Discussionmentioning
confidence: 99%